Archaeological and chemical investigation on mortars and bricks from a necropolis in Braga, Northwest of Portugal - Fragata, Ana (2021)
This investigation intends to study and characterize the mortars and bricks from walls and floors used in the funerary nucleus of the archaeological site of Dr. Gonçalo Sampaio Street (Braga, Portugal), associated with the Via XVII necropolis of the Bracara Augusta Roman city. The diversity of the funeral structures and their exceptional state of conservation make this sector of the necropolis an unprecedented case and a reference site in the archaeology of Braga, a determinant for its conservation and musealization. Nineteen mortars samples were analysed by X-ray Fluorescence. The results showed clear chemical composition differences among coating and floor mortars (CFM), masonry mortars (MM) and bricks (B) groups of samples. The chemical affinity between CFM from the V to IV centuries, CFM from the IV to V centuries, MM from brick walls (IV–V centuries), MM from stone walls (V–VII centuries) and B from the IV to V centuries samples were confirmed by statistical analyses. Their composition was distinctly related to the use of different raw materials, according to their chronological context; in mortars, according to their function in the structures; and in some samples, from contamination.